PEMBERIAN MINYAK IKAN LEMURU (Sardinella longiceps) SEBAGAI ANTI DISLIPIDEMIA MELALUI PENINGKATAN HDL PADA TIKUS WISTAR - Sri Wahjuni (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2011)
Changes in consumption behaviour to instant food can cause various health problems, such as obesity, dislipidemia, and atheroschlerosis. A study was conducted to investigate sardinella longiceps oil as anti dislipidemia through increasing HDL-C levels.This is a true experimental with randomized pre and posttest control group designs, emplyoying 50 Wistar rats grouped into five groups, i.e. control group (0% fish oil), treatment 1 group (10% fish oil), treatment 2 group (15% fish oil), treatment 3 group (20% fish oil), and treatment 4 group (25% sardinella longiceps oil). This research observed that intake of 20% sardinella longiceps oil resulted in the higest significant increase of HDL-C of 22.78 % (from 55.97 ±1.25 to 68.72 ± 6.25 mg/dL) for dislipidemia study. Therefore, it can be concluded that intake of sardinella longiceps oil in Wistar rat acts as anti dislipidemia by increasing the HDL-C levels. Further research is required to determine whether the application of sardinella longiceps on human will result in a simillar way, as anti inflammation and anti dislipidemia.